How to interpret the results of a sleep study - Deepak Shrivastava; Syung Jung; Mohsen Saadat; Roopa Sirohi; Keri Crewson (Greater Baltimore Medical Center, 2014)
With an increased level of awareness of sleep disorders among the public, there has been an increase in requests for sleep studies, and consequently, more referrals made to sleep specialists by primary care physicians and other health care providers. Understanding technical and clinical information provided in the sleep study report is crucial. It offers significant insight in to sleep pathophysiology in relation to patient symptoms. The purpose of this article is to provide a simple and easy method to interpret the reported results of polysomnography for primary care physicians. This will facilitate better understanding and management of patients with sleep disorders and related complications.